Pengaruh Permainan Modifikasi Terhadap Motorik Kasar Dan Halus Anak Usia Dini 4-5 Tahun Di PAUD Mutiara Kasih Desa Buduran Kabupaten Sidoarjo - Barki Muslim, Muhammad Zaidan; Kumaat, Noortje Anita; Sudijandoko, Andun; Yuliastrid, Dita (Universitas Hamzanwadi, 2024)
The problem of this research is that generation z or gen z prefers to stay at home playing gadgets or watching television, of course for children this phenomenon is very dangerous for the progress and stimulus of their development both health, mental and physical children. The purpose of this study was to examine the effect of sports modification games on early childhood motoric 4-5 years. This study uses quantitative research methods with a quasi-experimental approach or quasi-experimental desing. The population and sample in this study totalled 24 students. In this study using onegrup pretest and posttes type of research. This study uses a child motor test instrument from the director general of sports depdiknas. The results of the calculation show the results of the experimental posttest group are higher (M = 23.0000, SD = 1.47710) showing a level to the control group (t = 4.615, df = 22) compared to the control group (M = 19.9167, SD = 1.78164) from these results a significant increase in the experimental class is obtained. conclusion there is a significant effect on the provision of modified games on early childhood motor development.